Chiral carbon-based nanomaterials, methods of making and using the same

CN122954672APending Publication Date: 2026-10-23SUZHOU UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611312183.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-27
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

但现有手性碳基纳米材料的研究仍主要集中在手性识别、荧光检测、催化调控与酶活性调节等场景,对于手性结构是否能够影响纳米材料与细胞之间的相互作用,及其是否能产生构型选择性的氧化应激保护作用,目前仍缺乏系统性研究

Benefits of technology

[0016]本发明的有益效果在于:本申请提供的手性碳基纳米材料,具有明确的圆二色手性光谱特征与极高的细胞生物相容性,在宽浓度范围内表现出极低的细胞毒性;并能够利用手性构型与生物靶标之间的立体选择性相互作用,高效靶向淬灭细胞内活性氧(ROS)等氧化性物种,显著缓解氧化应激导致的细胞损伤并大幅提升受损细胞存活率,展现出卓越的抗细胞衰老与保护性能,在制备抗氧化应激产品或抗衰老产品中,如功能性化妆品、医药及保健品等,具有广阔的应用价值。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122954672A_ABST
    Figure CN122954672A_ABST
Patent Text Reader

Abstract

The application relates to the field of nanobiotechnology, in particular to a chiral carbon-based nanomaterial with antioxidant stress activity and a preparation method and application thereof. The chiral carbon-based nanomaterial comprises a graphite-phase carbon nanostructure and chiral cysteine molecules covalently connected to the surface of the graphite-phase carbon nanostructure. The chiral carbon-based nanomaterial has clear circular dichroism chiral spectral characteristics and extremely high cell biological compatibility, and exhibits extremely low cytotoxicity in a wide concentration range; and can utilize the stereoselective interaction between the chiral configuration and a biological target to efficiently target and quench intracellular active oxygen species such as oxidative species, significantly relieve cell damage caused by oxidative stress and greatly improve the survival rate of damaged cells, and exhibit excellent anti-cell aging and protection performance, and has wide application value in the preparation of antioxidant stress products or anti-aging products.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of nanobiotechnology, specifically to a chiral carbon-based nanomaterial with antioxidant properties, its preparation method, and its applications. Background Technology

[0002] With the deepening of population aging and increasing environmental oxidative pressure, delaying aging, improving skin health, and maintaining cellular homeostasis have become core research directions in the field of life and health. Existing research has confirmed that oxidative stress is one of the core causes of cellular aging: when the body is exposed to ultraviolet radiation, environmental pollution, inflammatory stimulation, or metabolic abnormalities, intracellular reactive oxygen species (ROS) accumulate abnormally. Excessive ROS directly triggers lipid peroxidation, protein oxidative modification, and DNA damage, ultimately leading to decreased cellular function and the manifestation of aging phenotypes. Currently, materials used for anti-oxidation and anti-aging mainly include vitamins, polyphenolic natural products, and some nano-antioxidant materials. However, these materials generally suffer from poor stability, short duration of action, and low cellular utilization efficiency. In recent years, carbon-based nanomaterials have become a research hotspot in the field of novel antioxidant materials due to their excellent electron transfer capabilities, chemical stability, and surface modifiability.

[0003] Carbon quantum dots (CDs), as typical carbon-based nanomaterials, possess advantages such as small size, high water dispersibility, and good biocompatibility. Studies have shown that the surface structure and optical properties of carbon dots can be precisely controlled by introducing nitrogen- and sulfur-containing precursors; cysteine, in particular, is often used to construct heteroatom-containing carbon-based nanomaterials because it simultaneously carries amino, carboxyl, and thiol groups. Meanwhile, the induction of chiral molecules to construct chiral carbon dot materials has become an important research direction in the field of nanomaterials. However, current research on chiral carbon-based nanomaterials mainly focuses on chiral recognition, fluorescence detection, catalytic regulation, and enzyme activity modulation. Systematic research is still lacking on whether chiral structures can affect the interaction between nanomaterials and cells, and whether they can produce configuration-selective oxidative stress protection. In particular, existing technologies for preparing chiral carbon dots using cysteine ​​and citric acid only focus on the chiral optical properties and catalytic performance of the materials themselves. They neither reveal the functional differences of carbon-based nanomaterials with different chiral configurations under cellular oxidative damage environments, nor disclose the technical pathways for using chiral carbon-based nanomaterials with specific configurations to enhance cellular antioxidant capacity and intervene in oxidative stress-induced aging.

[0004] Therefore, there is an urgent need to develop a chiral carbon-based nanomaterial that can utilize chiral structures to regulate cellular oxidative stress responses and possesses excellent antioxidant and anti-aging activities. Summary of the Invention

[0005] The purpose of this invention is to provide a chiral carbon-based nanomaterial with antioxidant properties. This chiral carbon-based nanomaterial has good cell compatibility and can effectively reduce intracellular ROS levels and improve cell survival under oxidative damage conditions.

[0006] To achieve the above objectives, the present invention provides the following technical solution: a chiral carbon-based nanomaterial with antioxidant properties, comprising a graphite-phase carbon nanostructure and chiral cysteine ​​molecules covalently linked to the surface of the graphite-phase carbon nanostructure; wherein the chiral cysteine ​​molecules are L-cysteine ​​molecules and / or D-cysteine ​​molecules; The chiral carbon-based nanomaterials exhibit circular dichroism absorption peaks in the range of 200 nm to 275 nm.

[0007] Furthermore, the surface of the chiral carbon-based nanomaterial has amino, carboxyl, and hydroxyl functional groups as well as CS covalent bonds; Furthermore, the chiral carbon-based nanomaterials are monodisperse particles with an average particle size distribution in the range of 1 nm to 5 nm.

[0008] Furthermore, the ultraviolet-visible absorption spectrum of the chiral carbon-based nanomaterial has characteristic absorption peaks at 242 nm to 252 nm and 345 nm to 355 nm, and under excitation at wavelengths of 375 nm to 395 nm, it has a maximum fluorescence emission peak at 455 nm to 465 nm.

[0009] This application provides the application of the above-mentioned chiral carbon-based nanomaterials in the preparation of anti-oxidative stress products or anti-aging products. The chiral carbon-based nanomaterials are used to reduce the level of reactive oxygen species in cells under oxidative stress conditions and improve the survival rate of oxidatively damaged cells.

[0010] Furthermore, the oxidative stress is induced by hydrogen peroxide.

[0011] Furthermore, the chiral carbon-based nanomaterials are used to scavenge one or more of reactive oxygen species, ABTS radicals, and DPPH radicals.

[0012] Furthermore, the chiral cysteine ​​molecule is a D-cysteine ​​molecule, which enables the chiral carbon-based nanomaterial to increase the survival rate of oxidatively damaged cells to 80% or more.

[0013] Furthermore, the antioxidant stress product or anti-aging product is a cosmetic composition, skin care composition, health product, or pharmaceutical composition.

[0014] This application provides a method for preparing the above-mentioned chiral carbon-based nanomaterials, comprising: S1. Citric acid is heat-treated at 170℃-190℃ to form a carbonized intermediate; S2. Add chiral cysteine ​​molecules to the carbonized intermediate and carry out a thermal polymerization reaction at 130℃-160℃ to promote the chiral cysteine ​​molecules to participate in the formation of carbon structure, and obtain a solid-phase melt thermal polymerization product. S3. The solid-phase molten thermal polymerization product is sequentially subjected to water dispersion, filtration and dialysis to obtain the chiral carbon-based nanomaterial.

[0015] Further, the mass ratio of citric acid in step S1 to chiral cysteine ​​molecules in step S2 is 1:(0.8-1.2). In step S3, during the dialysis process, the molecular weight cutoff of the dialysis bag used is 500 Da-1000 Da.

[0016] The beneficial effects of this invention are as follows: The chiral carbon-based nanomaterials provided in this application have distinct circular dichroism chiral spectral characteristics and extremely high cell biocompatibility, exhibiting extremely low cytotoxicity over a wide concentration range; and can utilize the stereoselective interaction between chiral configuration and biological targets to efficiently target and quench intracellular reactive oxygen species (ROS) and other oxidative species, significantly alleviating cell damage caused by oxidative stress and greatly improving the survival rate of damaged cells, demonstrating excellent anti-cellular aging and protective properties. It has broad application value in the preparation of anti-oxidative stress products or anti-aging products, such as functional cosmetics, pharmaceuticals and health products.

[0017] The chiral carbon-based nanomaterials provided in this application introduce chiral cysteine ​​molecules in situ during the formation of carbon-based nanostructures, enabling the carbon nanomaterial framework to obtain a clear and stable chiral spectral response. At the same time, the surface of the material is covalently modified with abundant active groups such as amino, carboxyl, hydroxyl and sulfur-containing covalent bonds, thereby endowing the material with excellent single electron transfer ability, broad-spectrum free radical scavenging activity and oxidizing species reduction performance.

[0018] The preparation method provided in this application is simple, operates under mild conditions, and uses readily available raw materials, making it highly feasible. Using citric acid and L-cysteine ​​or D-cysteine ​​as raw materials, this method yields chiral carbon-based nanomaterials with uniform particle size through pre-carbonization, chiral cysteine ​​thermal polymerization, filtration, and dialysis. It eliminates the need for complex surface functionalization or multi-step chemical modification processes, resulting in low production costs and high batch stability. This provides a solid and feasible industrialization technology path for developing novel anti-cellular oxidative stress and anti-aging products.

[0019] The above description is merely an overview of the technical solution of the present invention. In order to better understand the technical means of the present invention and to implement it in accordance with the contents of the specification, the preferred embodiments of the present invention are described in detail below with reference to the accompanying drawings. Attached Figure Description

[0020] Figure 1 Transmission electron microscope (TEM) images and particle size distribution diagrams of the chiral carbon-based nanomaterials prepared in Examples 1 and 2 of this invention; Figure 2 The circular dichroism (CD) spectra of the chiral carbon-based nanomaterials prepared in Examples 1 and 2 of this invention are shown below. Figure 3 The Fourier transform infrared (FT-IR) absorption spectra of the chiral carbon-based nanomaterials prepared in Examples 1 and 2 of this invention are shown below. Figure 4 The following are the ultraviolet-visible (UV-Vis) absorption spectra of the chiral carbon-based nanomaterials prepared in Examples 1 and 2 of this invention; Figure 5 The fluorescence excitation and emission spectra of the chiral carbon-based nanomaterials prepared in Examples 1 and 2 of this invention are shown. Figure 6 This is a comparison chart of the in vitro antioxidant properties of carbon-based nanomaterials prepared in Examples 1-3 and Comparative Example 1 of the present invention; Figure 7 The bar chart shows the biotoxicity evaluation of the chiral carbon-based nanomaterials prepared in Examples 1 and 2 of this invention on HaCaT cells. Figure 8 Bar charts are used to evaluate the protective effect (cell survival rate) of carbon-based nanomaterials prepared in Examples 1-3 and Comparative Example 1 against H2O2-induced oxidative damage and aging of HaCaT cells. Figure 9 Laser confocal microscopy fluorescence images of chiral carbon-based nanomaterials prepared in Examples 1 and 2 of this invention to alleviate H2O2-induced cellular oxidative stress and aging. Detailed Implementation

[0021] The technical solutions of the present invention will now be clearly and completely described with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention. Furthermore, the technical features involved in the different embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0022] A preferred embodiment of this application discloses a chiral carbon-based nanomaterial with antioxidant properties. This chiral carbon-based nanomaterial comprises a graphitic carbon nanostructure and chiral cysteine ​​molecules covalently linked to the surface of the graphitic carbon nanostructure. Preferably, the chiral cysteine ​​molecules are L-cysteine ​​and / or D-cysteine ​​molecules, more preferably D-cysteine ​​molecules. This chiral carbon-based nanomaterial exhibits circular dichroism absorption peaks in the 200 nm–275 nm range. Through surface covalent bonding modification, the chiral configuration information of the chiral cysteine ​​molecules is efficiently and stably transferred to the graphitic conjugated carbon nanostructure, giving the resulting chiral carbon-based nanomaterial a long-lasting and stable chiral stereocenter. Compared to traditional achiral carbon-based materials, this chiral carbon-based nanomaterial can utilize its unique chiral spatial configuration to generate highly specific stereoselective interactions with the microenvironment of living cells, significantly enhancing its targeted regulation of intracellular oxidative stress and reactive oxygen species metabolic pathways, thereby endowing the chiral carbon-based nanomaterial with excellent bio-antioxidant and cell-protective properties.

[0023] In one embodiment, the surface of this chiral carbon-based nanomaterial is connected with hydrophilic functional groups such as amino, carboxyl, hydroxyl, and amide groups, forming stable CS covalent bonds in its chemical framework. The abundant surface hydrophilic groups significantly enhance its water solubility and colloidal dispersion stability, and contribute to the construction of high-density active catalytic and adsorption sites, which facilitates electron transfer, rapid free radical capture, and efficient quenching of oxidative species. This chiral carbon-based nanomaterial exhibits highly uniform monodisperse nanoparticles with an average particle size distribution in the range of 1 nm to 5 nm. The small nanoscale size endows it with excellent transmembrane permeability, which helps enhance its interaction with the cellular microenvironment, enabling it to efficiently enter the cell and exert outstanding cellular antioxidant stress and anti-aging protective functions.

[0024] In one embodiment, the chiral carbon-based nanomaterial exhibits characteristic absorption peaks in the UV-Vis absorption spectrum at 242 nm–252 nm and 345 nm–355 nm, and a maximum fluorescence emission peak at 455 nm–465 nm when excited at wavelengths of 375 nm–395 nm. The characteristic absorption peak at 242 nm–252 nm corresponds to the spc atoms within the carbon core framework. 2 Hybrid conjugate domain Electron transitions, with absorption peaks in the 345 nm–355 nm range corresponding to chiral functional groups (such as carboxyl / amide groups) associated with surface modifications. This transition indicates that the chiral carbon-based nanomaterial possesses a stable carbon structure and surface chemical environment. Simultaneously, its inherent excellent fluorescence emission properties endow this chiral carbon-based nanomaterial with functions such as in-situ fluorescence tracing, intracellular dynamic distribution monitoring, and fluorescence bioimaging, while simultaneously exerting antioxidant / anti-aging bioactivity, significantly expanding its translational application potential in biomedical diagnosis and treatment and multifunctional cosmetic formulations.

[0025] One embodiment provides the application of the aforementioned chiral carbon-based nanomaterials in the preparation of anti-oxidative stress products or anti-aging products. These chiral carbon-based nanomaterials can reduce intracellular reactive oxygen species (ROS) levels under oxidative stress conditions and improve the survival rate of oxidatively damaged cells. This embodiment achieves a synergistic effect between the structural stability of graphite carbon nanomaterials and the specific biological activity of chiral molecules by covalently modifying the surface of graphite-phase carbon nanostructures with chiral cysteine ​​molecules. The resulting chiral carbon-based nanomaterials not only possess excellent and durable in vitro free radical scavenging activity but also can target and regulate the intracellular redox microenvironment through stereoselective action. Under oxidative stress, they significantly reduce intracellular ROS accumulation, reverse cellular oxidative damage, and greatly improve cell survival rate, exhibiting excellent anti-cellular aging and protective effects. This provides a material system with transformational value for the development of novel targeted antioxidant agents, anti-aging skincare products, and pharmaceuticals.

[0026] In one embodiment, oxidative stress is induced by hydrogen peroxide (H2O2). This chiral carbon-based nanomaterial can effectively alleviate H2O2-induced cellular oxidative damage, reduce intracellular ROS accumulation, and improve cell activity, demonstrating good cellular antioxidant protection capabilities.

[0027] In one embodiment, the chiral cysteine ​​molecule is preferably a D-cysteine ​​molecule, enabling the chiral carbon-based nanomaterial to increase the survival rate of oxidatively damaged cells to over 80%. This chiral carbon-based nanomaterial effectively improves the survival rate of oxidatively damaged cells, allowing them to maintain high biological activity under oxidative stress. Compared to traditional antioxidant materials that only possess free radical scavenging capabilities, this chiral carbon-based nanomaterial not only scavenges oxidative substances at the chemical level but also exerts a protective effect at the cellular level, demonstrating superior anti-oxidative stress and anti-aging effects.

[0028] In one embodiment, the chiral carbon-based nanomaterial possesses broad-spectrum free radical scavenging capabilities, enabling it to scavenge one or more of reactive oxygen species (such as hydroxyl radicals), ABTS radicals, and DPPH radicals. The surface of this chiral carbon-based nanomaterial is rich in active functional groups, which can rapidly deplete oxidizing substances within the system through various mechanisms such as synergistic electron transfer, hydrogen atom transfer / free radical quenching, and complexation at surface-active catalytic sites, significantly enhancing its antioxidant protective efficacy. This provides a broad application basis for its use in the preparation of functional cosmetics, skincare products, health supplements, and antioxidant / anti-aging drug compositions.

[0029] In one embodiment, the antioxidant stress product or anti-aging product includes cosmetic compositions, skin care compositions, health products, and pharmaceutical compositions, etc.

[0030] One embodiment provides a method for preparing the above-mentioned chiral carbon-based nanomaterials, characterized in that it includes: S1. Citric acid is heat-treated at 170℃-190℃ to form a carbonized intermediate; S2. Add chiral cysteine ​​molecules to the carbonization intermediate and carry out a thermal polymerization reaction at 130℃-160℃ to promote the participation of chiral cysteine ​​molecules in the formation of carbon structure, and obtain solid-phase melt thermal polymerization product. S3. The solid-phase molten thermal polymerization product is sequentially subjected to water dispersion, filtration, and dialysis to obtain chiral carbon-based nanomaterials. This preparation method uses citric acid monohydrate as the carbon source framework and chiral cysteine ​​as the chiral source and modifying group. It achieves precise and controllable construction of chiral carbon-based nanomaterials through a staged thermal polymerization reaction involving first high-temperature carbonization nucleation and then controlled-temperature melting for chiral covalent bonding. This two-step temperature-controlled process is mild, avoiding chiral racemization or excessive carbonization decomposition caused by prolonged high-temperature reactions. The process is short, simple, and controllable, with excellent batch-to-batch reproducibility, demonstrating significant cost advantages and potential for industrial-scale production.

[0031] In one embodiment, the mass ratio of citric acid to chiral cysteine ​​molecules in step S1 is 1:(0.8-1.2). By controlling the mass ratio of citric acid to chiral cysteine, chiral molecules can effectively participate in carbon structure formation and help regulate the degree of chiral modification and the content of active functional groups on the material surface. In step S3, the molecular weight cutoff of the dialysis bag used in the dialysis process is 500Da-1000Da. Suitable dialysis conditions can effectively remove unreacted small molecules and byproducts, thereby obtaining structurally stable and high-performance chiral carbon-based nanomaterials. This chiral carbon-based nanomaterial combines the stability of graphite carbon structure, the chiral characteristics of cysteine ​​molecules, and the surface activity advantages of nanomaterials. It can effectively scavenge various oxidative free radicals, reduce intracellular ROS levels, and protect cells from oxidative stress-induced damage and aging.

[0032] Example 1

[0033] S1. Weigh 5g of citric acid monohydrate and add it to a round-bottom flask. Heat treat it at 180℃ to cause the citric acid to undergo dehydration condensation and preliminary carbonization reaction. After heat treatment for 30 minutes, the pre-carbonized intermediate, i.e., carbon core, is obtained.

[0034] S2. Add 5g of L-cysteine ​​molecules to the pre-carbonized intermediate and heat in an oil bath at 150℃ for 60min to allow L-cysteine ​​to participate in the thermal polymerization reaction and introduce chiral amino acid molecules during the carbon structure formation process to obtain a solid-phase melt thermal polymerization product, namely the crude product of L-cysteine-modified carbon-based nanomaterials.

[0035] S3. The solid-phase molten thermal polymerization product was added to 20 mL of ultrapure water for dispersion. After sufficient dispersion, it was filtered to remove unreacted large particles and insoluble impurities. Subsequently, it was purified by dialysis using a dialysis bag with a molecular weight cutoff of 500-1000 Da for 3 days, during which the ultrapure water was changed daily. Finally, L-cysteine-modified chiral carbon-based nanomaterials, denoted as L-CDs, were obtained.

[0036] Example 2

[0037] The difference between this embodiment and Example 1 is that in step S2, 5g of D-cysteine ​​is used instead of 5g of L-cysteine. After reaction and purification under the same conditions, D-cysteine-modified chiral carbon-based nanomaterials, denoted as D-CDs, are obtained.

[0038] Example 3

[0039] The difference between this embodiment and Example 1 is that in step S2, 2.5g of D-cysteine ​​molecules and 2.5g of L-cysteine ​​molecules are added to the pre-carbonized intermediate. After reaction and purification under the same conditions, racemic cysteine-modified carbon-based nanomaterials, denoted as L / D-CDs, are obtained.

[0040] Comparative Example 1 5 g of citric acid monohydrate was weighed into a round-bottom flask and heat-treated at 180 °C for 30 min to obtain a pre-carbonized intermediate. The pre-carbonized intermediate was dissolved in 20 mL of ultrapure water for dispersion. Filtration was then performed to remove large particles and unreacted precipitates. Dialysis was then performed using a dialysis bag with a molecular weight cutoff of 500-1000 Da for 3 days, with the ultrapure water changed daily. Finally, unmodified carbon-based nanomaterials, denoted as A-CDs, were obtained.

[0041] The physical, chemical, and optical properties of the chiral carbon-based nanomaterials prepared in Examples 1 and 2 were characterized and analyzed using transmission electron microscopy (TEM), circular dichroism spectroscopy (CD), Fourier transform infrared spectroscopy (FTIR), ultraviolet-visible absorption spectroscopy (UV-Vis), and fluorescence spectroscopy, respectively. The results are as follows: Figures 1-5 As shown.

[0042] like Figure 1 As shown, the chiral carbon-based nanomaterials L-CDs prepared in Example 1 and D-CDs prepared in Example 2 are both regular spherical particles with good dispersion and uniform size distribution, and no obvious agglomeration was observed. The average particle size of L-CDs is about 2.55 nm, and the average particle size of D-CDs is about 2.36 nm.

[0043] like Figure 2 As shown, both L-CDs and D-CDs exhibit a clear circular dichroism spectral response in the 200 nm–275 nm range, and their CD signals show a mirror-symmetric relationship. This indicates that by introducing cysteine ​​molecules with different configurations, chiral information is effectively transferred to carbon nanostructures, forming stable chiral carbon-based nanomaterials.

[0044] like Figure 3 As shown, L-CDs and D-CDs have similar infrared absorption characteristics. At 3420 cm⁻¹ -1 The absorption peak near 2940 cm⁻¹ corresponds to the OH stretching vibration; -1 The absorption peak corresponds to the CH / NH vibration; at 1700 cm⁻¹ -1 The absorption peak corresponds to the C=O stretching vibration; at 1400 cm⁻¹ -1 With 1240cm-1 The absorption peaks correspond to the bending vibrations of CN and OH, respectively; at 1050 cm⁻¹ -1 The absorption peak corresponds to the CO bond; at 660 cm⁻¹ -1 The presence of CS bond characteristic vibrations indicates that chiral cysteine ​​successfully participates in the carbon structure formation process, and can be firmly linked to the surface of the pre-carbonized intermediate through covalent bonds, thus endowing the material with abundant hydrophilic active groups such as carboxyl, hydroxyl, amino, and amide groups.

[0045] like Figure 4 As shown, the UV-Vis absorption spectra of L-CDs and D-CDs exhibit high overall consistency, indicating that the two chiral carbon-based nanomaterials constructed using L-cysteine ​​or D-cysteine ​​share similar carbon-based host structures and surface electronic structures. Both L-CDs and D-CDs show a distinct characteristic absorption peak at approximately 247 nm, which can be attributed to the sp(s) content in carbon-based nanomaterials. 2 hybrid carbon structure The transition indicates that the obtained material possesses a corresponding conjugated carbon structure; characteristic absorption peaks appear at approximately 350 nm, which can be attributed to oxygen- and nitrogen-containing functional groups on the material surface. The transition corresponds to the presence of functional groups such as carboxyl, carbonyl, and amide groups on the material surface. This result indicates that cysteine ​​participates in the formation of carbon-based nanomaterials and introduces corresponding hydrophilic active functional groups onto the surface of the resulting carbon-based nanostructures.

[0046] like Figure 5 As shown, both L-CDs and D-CDs can produce blue fluorescence in the visible light region under ultraviolet or near-ultraviolet light excitation, indicating that both chiral carbon-based nanomaterials possess good fluorescence and luminescence properties. Figure 5 As shown in figure a, L-CDs exhibit a maximum fluorescence emission peak at 459.23 nm under 380.00 nm excitation conditions; as Figure 5 As shown in b, D-CDs exhibit a maximum fluorescence emission peak at 458.17 nm under 391.00 nm excitation conditions. Both L-CDs and D-CDs possess both antioxidant activity and fluorescence properties, enabling them to reduce oxidative stress and protect cells from oxidative damage while providing optical signals for observing the distribution, uptake, and localization of materials at the cellular level. This provides a foundation for their visualization evaluation and mechanism of action research in anti-oxidative stress or anti-aging products.

[0047] Using the L-CDs prepared in Example 1, the D-CDs prepared in Example 2, the racemic L / D-CDs prepared in Example 3, and the achiral, unmodified carbon-core A-CDs prepared in Comparative Example 1 as test objects, and an equal volume of ultrapure water as a parallel control, their scavenging abilities against oxidizing substances such as potassium permanganate, hydroxyl radicals, ABTS radicals, and DPPH radicals were tested. The results are as follows: Figure 6 As shown.

[0048] The determination of potassium permanganate reducing power included: preparing L-CDs obtained in Example 1, D-CDs obtained in Example 2, L / D-CDs obtained in Example 3, and A-CDs obtained in Comparative Example 1 into test samples with concentrations of 100 μg / mL, 200 μg / mL, 400 μg / mL, 500 μg / mL, and 1000 μg / mL, respectively. Then, 100 μL of each test sample was mixed with 100 μL of potassium permanganate solution and reacted in the dark for 60 min, serving as the experimental group. An equal volume of ultrapure water was used to replace the test samples, serving as the control group. The scavenging rate was calculated using the difference in absorbance at 525 nm after the reaction. KMnO4 scavenging rate % = (K0 - K) S ) / K0×100%; In the formula, K0 is the absorbance of the control group at 525 nm; K S The absorbance of the experimental group at 525 nm is given.

[0049] The determination of hydroxyl radical (·OH) scavenging ability included: preparing L-CDs obtained in Example 1, D-CDs obtained in Example 2, L / D-CDs obtained in Example 3, and A-CDs obtained in Comparative Example 1 into test samples with concentrations of 200 μg / mL, 400 μg / mL, 600 μg / mL, 800 μg / mL, and 1000 μg / mL, respectively. Reaction reagents were added to a 96-well plate to generate hydroxyl radicals in situ; subsequently, salicylic acid was added, which reacted with the unscavenged hydroxyl radicals to generate the chromogenic product 2,3-dihydroxybenzoic acid. Then, the test sample solutions were added, thoroughly mixed, and incubated at 37°C for 20 min. An equal volume of ultrapure water was used as a control group. After the reaction, the absorbance of each experimental group and the control group at 510 nm was measured using a microplate reader, and the scavenging rate of each sample for hydroxyl radicals was calculated according to the following formula: ·OH removal rate % = (H0 - H S ) / H0×100%; In the formula, H0 represents the absorbance of the control group at 510 nm; H S The absorbance of the experimental group at 510 nm is given.

[0050] ABTS free radical cation (ABTS· + The scavenging ability determination included: preparing L-CDs obtained in Example 1, D-CDs obtained in Example 2, L / D-CDs obtained in Example 3, and A-CDs obtained in Comparative Example 1 into test samples with concentrations of 50 μg / mL, 100 μg / mL, 150 μg / mL, 200 μg / mL, and 250 μg / mL, respectively. ABTS powder and potassium persulfate powder were weighed and dissolved in ultrapure water to prepare 7.4 mM ABTS stock solution and 2.6 mM potassium persulfate stock solution, respectively. 1 mL of ABTS stock solution and 1 mL of potassium persulfate stock solution were thoroughly mixed and allowed to stand for 12 h at room temperature in the dark to obtain ABTS stock solution. An appropriate amount of ABTS stock solution was diluted with PBS buffer to an absorbance of 0.65–0.75 at 734 nm, which was then used as a freshly prepared ABTS working solution. During the test, 200 μL of ABTS working solution and 10 μL of each concentration of the test sample solution were added to a 96-well plate as the experimental group. After thorough mixing, the mixture was reacted at room temperature in the dark for 5 min. Simultaneously, an equal volume of ultrapure water was used to replace the test sample solution as the control group. The scavenging rate of the material for ABTS radical cations was calculated using the difference in absorbance at 734 nm between the experimental and control groups after the reaction. ABTS· + Clearance rate % = (A0 - A) S ) / A0×100%; In the formula, A0 is the absorbance of the control group at 734 nm; A S The absorbance of the experimental group at 734 nm is given.

[0051] The determination of DPPH free radical scavenging ability included: preparing test samples with concentrations of 25 μg / mL, 50 μg / mL, 100 μg / mL, 200 μg / mL, and 400 μg / mL, respectively, using L-CDs prepared in Example 1, D-CDs prepared in Example 2, L / D-CDs prepared in Example 3, and A-CDs prepared in Comparative Example 1. DPPH powder was weighed and dissolved in anhydrous ethanol to prepare a 0.8 mM DPPH working solution. For detection, 100 μL of DPPH working solution and 100 μL of each concentration of test sample were added to a 96-well plate as the experimental group. After thorough mixing, the mixture was reacted at 37°C in the dark for 30 min. Simultaneously, an equal volume of ultrapure water was used to replace the test samples as a blank control group; an equal volume of anhydrous ethanol was used to replace the DPPH working solution as a sample background control group, with all other conditions kept consistent. After the reaction was completed, the absorbance of each group at 517 nm was measured, and the scavenging rate of the material for DPPH free radicals was calculated according to the following formula: DPPH clearance rate % = (D0 - D) S +D c) / D0×100%; In the formula, D0 represents the absorbance of the blank control group at 517 nm; D S D represents the absorbance of each experimental group of test samples at 517 nm. c The absorbance at 517 nm represents the background control group of the corresponding test sample.

[0052] Depend on Figure 6 As shown in Figure a, L-CDs, D-CDs, and L / D-CDs all exhibited extremely strong concentration-dependent reducing abilities. When the concentration reached 500 μg / mL, the scavenging rate of KMnO4 approached 70%-80%; when the concentration increased to 1000 μg / mL, the scavenging rate exceeded 90%. In contrast, the unmodified A-CDs prepared in Comparative Example 1 showed scavenging rates below 10% at all concentrations. This indicates that cysteine ​​modification can significantly enhance the electron-donating capacity and oxide-reducing ability of carbon-based nanomaterials. Figure 6 As shown in b, the scavenging rates of ·OH by L-CDs, D-CDs, and L / D-CDs steadily increased with increasing concentration, reaching approximately 70% at 1000 μg / mL; while the scavenging rate of unmodified A-CDs was less than 15%. Figure 6 As shown in c, L-CDs, D-CDs, and L / D-CDs exhibit extremely high ABTS radical scavenging activity, achieving scavenging rates exceeding 80% at a low concentration of 50 μg / mL and approaching 90% at 250 μg / mL; while A-CDs only achieved scavenging rates of 12%-25% within the same concentration range. Figure 6 As shown in Figure d, at an extremely low concentration of 25 μg / mL, L-CDs, D-CDs, and L / D-CDs achieved a DPPH scavenging rate of over 70%, exceeding 90% at 200 μg / mL; while the scavenging rate of A-CDs remained consistently at an extremely low level of around 20%. This indicates that L-CDs, D-CDs, and L / D-CDs not only possess excellent reducing ability for KMnO4 but also exhibit excellent scavenging abilities for hydroxyl radicals, ABTS radicals, and DPPH radicals. This result demonstrates that cysteine ​​modification can endow carbon-based nanomaterials with excellent in vitro antioxidant activity.

[0053] To comprehensively evaluate the cell compatibility, in vitro antioxidant activity, and protective effect against H2O2-induced oxidative stress damage of the chiral carbon-based nanomaterials of this invention, human immortalized epidermal cells (HaCaT) were used as a cell model. Cytotoxicity evaluation and H2O2-induced oxidative damage protection experiments were conducted. The cell protective effect of the material was evaluated by cell viability and intracellular reactive oxygen species (ROS) levels. Experimental results are as follows: Figures 7-9 As shown.

[0054] The evaluation of cellular biotoxicity includes: using HaCaT cells as a cell model, with 1×10 4 Cells were seeded at a density of [number] cells / well in 96-well cell culture plates and cultured overnight in DMEM at 37°C and 5% CO2 to ensure full cell adhesion. Subsequently, culture medium containing different concentrations of L-CDs or D-CDs were added, with final concentrations of L-CDs at 200 μg / mL, 400 μg / mL, 600 μg / mL, 800 μg / mL, and 1000 μg / mL, respectively, and cultured for another 24 h. After incubation, the culture medium was aspirated, each well was washed three times with PBS buffer, and CellTiter-Lumi chemiluminescence assay reagent (CTL chemiluminescence reagent) was added. The cells were incubated at room temperature in the dark for 10 min, and the chemiluminescence intensity of each well was measured using a microplate reader. Relative cell viability was calculated using the following formula: Relative cell viability % = (C S -C0) / (C c -C0)×100%; In the formula, C S C0: Luminous intensity of the experimental group; C0: Luminous intensity of the blank group; C0: luminous intensity of the control ... c : The luminescence intensity of the cell control group.

[0055] Evaluation of H2O2-induced cellular oxidative damage and senescence: Using HaCaT cells as a model, the protective effects of various samples against H2O2-induced cellular oxidative stress and senescence were evaluated. The experiment included a normal blank control group, an H2O2 model group, an L-CDs protection group, a D-CDs protection group, an L / D-CDs protection group, and an A-CDs protection group. Specifically, L-CDs prepared in Example 1, D-CDs prepared in Example 2, L / D-CDs prepared in Example 3, and A-CDs prepared in Comparative Example 1 were added to the HaCaT cell culture system along with 0.1 mM H2O2 and incubated for 3 h. The normal blank control group did not receive H2O2 or the test materials, while the H2O2 model group received 0.1 mM H2O2 but no test materials. After incubation, the chemiluminescence intensity of cells in each group was detected using CellTiter-Lumi chemiluminescence assay, and the relative cell viability was calculated using the cell viability calculation method described above to evaluate the protective effects of different materials against H2O2-induced cellular oxidative damage. Simultaneously, the intracellular ROS level was detected using a DCFH-DA fluorescent probe. After entering the cell, DCFH-DA is acted upon by relevant intracellular enzymes to form an oxidizable fluorescent probe, the fluorescence intensity of which can be used to characterize changes in intracellular ROS levels. DAPI was used to fluorescently stain the cell nuclei to observe nuclear morphology and cell distribution. After staining, laser confocal scanning microscopy was used to acquire images of each group of cells, and changes in DCF green fluorescence and DAPI blue fluorescence signals were compared among the groups.

[0056] Depend on Figure 7 It was found that within a wide concentration range of 200-1000 μg / mL, the relative cell viability of HaCaT cells remained above 90% after 24 h of treatment with L-CDs and D-CDs, and no significant concentration-dependent decrease in cell viability was observed. This indicates that within this concentration range, L-CDs and D-CDs did not exhibit significant cytotoxicity to HaCaT cells and possessed good cell compatibility, providing a foundation for their further application in experiments protecting cells against oxidative stress and in the development of anti-oxidative stress and anti-aging products.

[0057] Depend on Figure 8It was found that, compared with the normal blank control group, the survival rate of HaCaT cells decreased significantly to approximately 35% after treatment with 0.1 mM H2O2, indicating that the established H2O2-induced oxidative damage model could effectively cause cellular oxidative damage. After intervention with unmodified A-CDs, the cell survival rate remained at approximately 34%, showing no significant improvement compared to the H2O2 model group. This indicates that unmodified carbon-based materials lack significant protective effects against H2O2-induced cell damage. In contrast, intervention with racemic L / D-CDs and L-CDs significantly increased the cell survival rate to 67% or higher, indicating that cysteine ​​modification can significantly enhance the protective effect of carbon-based nanomaterials against H2O2-induced cellular oxidative damage. Furthermore, intervention with D-CDs significantly increased the cell survival rate to 81% or higher, with a significantly better protective effect than the L-CDs, L / D-CDs, and A-CDs treatment groups. This result indicates that cysteine ​​modification can significantly enhance the protective effect of carbon-based nanomaterials against oxidative stress-damaged cells. At the same time, compared with L-CDs and racemic L / D-CDs, D-CDs showed a more significant cell protection effect, suggesting that chiral configuration may be involved in regulating the interaction between materials and cells and producing configuration-dependent biological effects.

[0058] Depend on Figure 9 It was found that the DCF green fluorescence signal of the normal blank control group cells was weak, indicating that intracellular ROS was maintained at a low level. After treatment with 0.1 mM H2O2, the DCF green fluorescence of the cells was significantly enhanced, indicating that H2O2 treatment led to a significant increase in intracellular ROS levels, resulting in a significant oxidative stress state. After intervention with L-CDs and D-CDs, the intracellular DCF green fluorescence signal was significantly weakened, indicating that both chiral carbon-based nanomaterials could reduce H2O2-induced intracellular ROS levels. Among them, the green fluorescence weakening was more significant in the D-CDs treatment group, indicating that D-CDs had a stronger effect on reducing intracellular ROS. At the same time, no obvious abnormalities were found in the overall morphology of the cell nucleus as shown by the blue fluorescence of DAPI in each group. Combined with the cell viability results, it can be concluded that L-CDs and D-CDs can alleviate H2O2-induced oxidative damage to cells while reducing intracellular ROS levels.

[0059] The chiral carbon-based nanomaterials prepared in this application exhibit good cell compatibility and can effectively reduce H2O2-induced intracellular ROS levels and improve cell survival under oxidative damage conditions, showing potential application in the preparation of anti-oxidative stress products or anti-aging products. Among them, D-CDs show particularly significant cell protective effects, indicating that the chiral configuration of chiral carbon-based nanomaterials has an important influence on their cellular antioxidant protective performance.

[0060] The technical features of the above embodiments can be combined in any way. For the sake of brevity, not all possible combinations of the technical features in the above embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0061] The embodiments described above are merely illustrative of several implementations of the present invention, and while the descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the invention patent. It should be noted that those skilled in the art can make various modifications and improvements without departing from the concept of the present invention, and these all fall within the protection scope of the present invention. Therefore, the protection scope of this invention patent should be determined by the appended claims.

Claims

1. A chiral carbon-based nanomaterial with antioxidant properties, characterized in that, It includes a graphite-phase carbon nanostructure and chiral cysteine ​​molecules covalently attached to the surface of the graphite-phase carbon nanostructure; the chiral cysteine ​​molecules are L-cysteine ​​molecules and / or D-cysteine ​​molecules; The chiral carbon-based nanomaterials exhibit circular dichroism absorption peaks in the range of 200 nm to 275 nm.

2. The chiral carbon-based nanomaterial as described in claim 1, characterized in that, The surface of the chiral carbon-based nanomaterial has amino, carboxyl, and hydroxyl functional groups as well as CS covalent bonds; Furthermore, the chiral carbon-based nanomaterials are monodisperse particles with an average particle size distribution in the range of 1 nm to 5 nm.

3. The chiral carbon-based nanomaterial as described in claim 1 or 2, characterized in that, The chiral carbon-based nanomaterial exhibits characteristic absorption peaks in the ultraviolet-visible absorption spectrum at 242 nm–252 nm and 345 nm–355 nm, and under excitation at wavelengths of 375 nm–395 nm, it exhibits a maximum fluorescence emission peak at 455 nm–465 nm.

4. The application of the chiral carbon-based nanomaterials according to any one of claims 1-3 in the preparation of antioxidant stress products or anti-aging products, characterized in that, The chiral carbon-based nanomaterials are used to reduce intracellular reactive oxygen species levels under oxidative stress and improve the survival rate of oxidatively damaged cells.

5. The application as described in claim 4, characterized in that, The oxidative stress was induced by hydrogen peroxide.

6. The application as described in claim 4, characterized in that, The chiral carbon-based nanomaterials are used to scavenge one or more of reactive oxygen species, ABTS radicals, and DPPH radicals.

7. The application as described in claim 4, characterized in that, The chiral cysteine ​​molecule is a D-cysteine ​​molecule, which enables the chiral carbon-based nanomaterial to increase the survival rate of oxidatively damaged cells to 80% or more.

8. The application as described in claim 4, characterized in that, The antioxidant stress product or anti-aging product is a cosmetic composition, skin care composition, health product or pharmaceutical composition.

9. A method for preparing the chiral carbon-based nanomaterial according to any one of claims 1 to 3, characterized in that, include: S1. Citric acid is heat-treated at 170℃-190℃ to form a carbonized intermediate; S2. Add chiral cysteine ​​molecules to the carbonized intermediate and carry out a thermal polymerization reaction at 130℃-160℃ to promote the chiral cysteine ​​molecules to participate in the formation of carbon structure, and obtain a solid-phase melt thermal polymerization product. S3. The solid-phase molten thermal polymerization product is sequentially subjected to water dispersion, filtration and dialysis to obtain the chiral carbon-based nanomaterial.

10. The method as described in claim 9, characterized in that, The mass ratio of citric acid in step S1 to chiral cysteine ​​molecules in step S2 is 1:(0.8-1.2). In step S3, during the dialysis process, the molecular weight cutoff of the dialysis bag used is 500 Da-1000 Da.